MURATTAL DAN MUJAWWAD AL-QUR’AN DI MEDIA SOSIAL - Masrurin, ‘Ainatu (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2019)
Qur’an as self-referential text within the word Quran and Qul represents the moral dimension involved. It is a dimension when the Quran frequently is applied as a narrative object in daily life by which, according to Frédéric Deny, it is called Performative. In aesthetic reception discourse, Qur’an as a text is placed as an object approached beautifully. For instance, it’s voiced by sound and rhythm called murattal or Mujawwad. The oldest quranic recording is found in 1855 by S Hurgronje in which it was a starting point for the Quran to recept digitally in media matters. Around 2000, Quranic Aesthetic reception in media tools Was widespread massively, then reading Qur’an in this time using Rythm isn’t a matter to be coached directly. By phenomenological approach, this research tries to mapping the typology as well as the history of the reader (Qori) who changes to use social media as a listener and appreciator by uploading his/her reading. The result shows that three aspects are influencing the reader’s acts in social media, 1) to show the existence of the Quran 2) religious narcism, 3) authoritative freedom. Keyword: Performative, Aesthetic Reception, Qari’, Social Media